A STUDY OFTHE PERCEPTION OF YOUTHS OF SOUTHERN RAJASTHAN ON PRADHAN MANTRI KAUSHAL VIKAS YOJANA - Prof. P. K.Singh, Naman Khandelwal, Rajiv Choudhary, (Chelonian Research Foundation, 2022)
The government of India's innovative Pradhan Mantri Kaushal Vikas Yojana intends to provide 24 lakh young Indians with relevant, industry-related, and skill-based training. After successfully completing the training and assessment, the trainees will receive a government certification and a monetary award under this system, which will aid them in finding employment for a better future. Thus, it was envisioned as a crucial step to provide young men and women with skill-based training so they could assist the country's anti-poverty initiatives and earn a living. Prime Minister Narendra Modi launched his effort for the growth of entrepreneurship opportunities and skill development with the support of the National Skill Growth Council of India (NSDC), which both met and exceeded expectations. Still, it will produce a more highly skilled workforce in the near future. It contributes to increased employment opportunities and revenue creation. In this study article, we have investigated a sample of 200 respondents from Southern Rajasthan in an effort to determine how young people perceive PMKVY. Likert statements were created to gauge respondents' perceptions, and a single hypothesis was put forth to gauge answer consistency. Keywords: Skill development, Skill-based training,NSDC, PMKVY.